The Role of Information and Electronic Transactions Law in Controlling Teacher Activities in the Digital World at SDN Cimanggis 03 Bogor - Aswin Fitriansyah; Adhi Susano; Tria Hadi Kusmanto (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2021)
Education, business, industry and other fields use social media in their work. Utilization of technology in accordance with its needs is facilitated with social media in the industrial era 5.0. All sectors use online media due to the covid-19 pandemic. Information and communication in social media there are restrictions to be done openly or not allowed to be done. The Information and Electronic Transactions Act (ITE Law) regulates the provisions of communication. Regulatory ratification to protect the public from cybercrime in cyberspace. Defamation, blasphemy and online threats are contained in the article of the law. Principals, teachers and employees are given counseling on the role of the law when interacting and communicating on social media in community service activities conducted.